Motility, Abnormality and Intact Plasma Membrane of Sexed Bali Bull Sperm in Different Equilibration Time - Yendraliza, Yendraliza; Handoko, Jully; Istiannah, Fadila (Buletin Peternakan, 2025)
The purpose of this study was to obtain the optimal equilibration time to produce quality frozen semen of sexed Bali bulls in Tris-yolk diluent. Semen was collected from two male Bali cows from artificial insemination center, Tenayan Raya. Semen was collected for 8 wk and used as a replicate of the study. The motility of the semen used was 70%. Sperm X and Y were separated with 10% and 30% bovine serum albumin (BSA). The diluent used was tris egg yolk. The research treatment was equilibration time (2, 3, 4, and 5 h). Parameters were measured after sperm separation, dilution and thawing after freezing. Parameters consisted of motility, abnormality and intact plasma membrane. Data analysis was performed using a group randomized design. The results showed that the equilibration times of 2, 3, 4 and 5 h were significantly different on motility, abnormality and intact plasma membrane. The value of motility and intact plasma membrane is significantly different from after separation, dilution and freezing of Bali sperm. The values of motility, abnormality and intact plasma membrane of sperm X and sperm Y were not significantly different. Conclusion, 2 h equilibration time can maintain motility, abnormality and intact plasma membrane of sperm X and sperm Y of Bali cattle.